Self-Collection of Vaginal Swabs Among Adolescent Girls in a School-Setting in East Africa - Francis, Suzanna C; Miiro, George; Nakuya, Kevin; Rutakumwa, Rwamahe; Nakiyingi-Miiro, Jessica; Nabaggala, Grace; Musoke, Saidat; Namakula, Juliet; Tanton, Clare; Torondel, Belen; Ross, David A; Weiss, Helen A (Sexually transmitted diseases, 2019)
Few studies have evaluated the acceptability of self-collected vaginal swabs among young women in sub-Saharan Africa, including in school settings. We evaluated the acceptability of 2 conditions for the self-collection of swabs in secondary schools in Entebbe, Uganda. Assenting girls with parental consent from 3 secondary schools were provided instructions for sampling, and randomly allocated to self-collection of vaginal swabs with or without nurse assistance to help with correct placement of the swab. Swabs were tested for bacterial vaginosis by Gram stain. Participants were followed up after 1 to 2 days and 1 to 2 weeks and invited for a qualitative interview. Overall 96 girls were enrolled (median age, 16 years; interquartile range, 15-17 years). At the first follow-up visit, participants in both arms reported that instructions for sample collection were easy to understand, and they felt comfortable with self-collection. Girls in the nurse assistance arm reported feeling less relaxed (27% vs. 50%, P = 0.02) than those in the arm without nurse assistance, but more confident that they collected the sample correctly (96% vs. 83%, P = 0.04). About half (47%) of participants agreed that self-sampling was painful, but almost all (94%) would participate in a similar study again. Qualitative data showed that participants preferred self-collection without nurse assistance to preserve privacy. Bacterial vaginosis prevalence was 14% (95% confidence interval, 8-22). In this setting, self-collection of vaginal swabs in secondary schools was acceptable and feasible, and girls preferred self-collection without nurse assistance. Self-collection of swabs is an important tool for the detection, treatment and control of reproductive tract infections in girls and young women.